Positive Perspective: The Role of Narsism and Job Stressors on Work Productivity at Muhammadiyah University of Makassar - Marhumi, Sitti; Nurinaya, Nurinaya; Amalia, Putri (SENTRALISASI, 2024)
Many have carried out comprehensive testing. High work demands, but not accompanied by a conducive work environment can affect a person's productivity. This research is very important considering that work productivity is a demand, especially for study programs as a driver for the development and progress of a study program. Study programs have very extreme working hours which often cause some individuals to become stressed. This research emphasizes narsism in negative perceptions, uses secondary data and tries to construct other dimensions of narsism through positive perceptions which can stimulate work productivity both individually and in the surrounding environment. The objectives of this research are focused on 1) obtaining empirical evidence of the influence of narsism and job stressors on work productivity, 2) To check the tendency for narcissistic behavior to have a negative or positive value on work productivity. The research was analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The research results show that Narsism has no effect on work productivity, while Job Stressors have a positive and significant effect on work productivity at the Muhammadiyah University of Makassar.